Distance Spectra of Some Double Join Operations of Graphs - B. J. Manjunatha; B. R. Rakshith; K. N. Prakasha; N. V. Sayinath Udupa (International Journal of Mathematics and Mathematical Sciences)
In literature, several types of join operations of two graphs based on subdivision graph, Q-graph, R-graph, and total graph have been introduced, and their spectral properties have been studied. In this paper, we introduce a new double join operation based on H1,H2-merged subdivision graph. We compute the spectrum of a special block matrix and then use it to describe the distance spectra of some double join operations of graphs. At last, we give several families of distance equienergetic graphs of diameter 3.